Paying agencies as part of environmental protection in rural areas in Poland - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2012)
One of the elements of effectively implementing environmental policies in rural areas in Poland is the smooth functioning of public administrative bodies. Within the administrative system, what is most important here are paying agencies, which are based on national and European-Union standards, and support the development of organic farming and environmental education. The scope of the activities of these agencies largely contributes to the growth of environmental awareness in Poland’s rural areas.